Educational leadership for organisational learning and improved student outcomes - Mulford, William (Studies in educational leadership, 2004)
The change in paradigm in our field is away from the great man or woman theory of leadership and the teacher in his or her own classroom to the development of learning communities which value differences and support critical reflection and encourage members to question, challenge, and debate teaching and learning issues. How to achieve such learning communities is far from clear, but we believe the areas of problem-based learning (PBL) and organizational learning (OL) offer valuable clues. The indications are that the successful educational restructuring agenda depends on teams of leaders, whole staffs and school personnel, working together (i.e., OL) linking evidence and practice in genuine collaboration (i.e., PBL). The book is unique in that it is both about and uses these two concepts.